MENUMBUHKAN GAYA HIDUP BERKELANJUTAN DENGAN HERO WASTE: APLIKASI EDUKASI PENGELOLAAN SAMPAH BAGI PESERTA DIDIK MI AT-TAUFIQ - Setiawan, Ricky; Zamania, Zeni Zakia; Firdausyi, Marsya Salsabila; Novitasari, Kartika; Amanda, Kartika Budi; Arianto, Riska Octavia (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2024)
The issue of accumulation of waste is an enduring and recurring debate in society, it has numerous disavantage on the environment and living organisms. 85% of all of those waste actually can be manageable. This data highlights the primary contributor to this problem is the lack of public awareness and responsibility in proper waste management. Therefore, community service by Hero Waste Team is being conducted to educate the principles and responsibilities of effective waste management as early as possible, particularly among elementary school students.The waste management education program will be executed using the Hero Waste application for MI At-Taufiq Surabaya students during the period from August to October 2023. The program comprises three phases: preparation, program implementation, and monitoring and evaluation. As a result of this community service, students will develop the waste management habits, it is proofed by the proper waste management practices and the establishment of waste habituation following appropriate procedures.